Small-scale bedforms and associated sediment transport in a macro-tidal lower shoreface. (1st August 2021) - Guerrero, Q.; Williams, M.E.; Guillén, J.; Lichtman, I.D.; Thorne, P.D.; Amoudry, L.O.
Abstract: Ripples and small-scale bedforms are ubiquitous in shallow water environments under the combined action of currents and waves. Small scale processes linked to their formation and migration are interconnected with sediment transport at larger scales (e.g. tens of metres to kilometres), both resulting in and being affected by large scale sediment transport and geomorphological evolution. The lower shoreface provides a key link between coasts and continental shelves, but the contribution of ripples and small-scale bedforms to sediment transport in this region has yet to be fully addressed. This work presents a study of sediment dynamic processes on the lower shoreface in the presence of small-scale bedforms. Observations were made during the winter of 2017 on the lower shoreface of Perranporth Beach, which is in the south west of the UK and exposed to Atlantic waves. The analysis of morphological expressions and the variability of ripples under waves, currents and wave-current conditions are assessed. Ripple morphology and associated dynamics are analysed for their potential contribution to the exchange of sediment between the lower and the upper shoreface. In the present study it was observed that even though ripples were evolving depending on the wave-current forcing, little ripple migration was observed due to low wave skewness. The implication is that ripple migration and bedload transport are only a small contribution to onshore sediment transport under low to moderate energy conditions. However, during more energetic conditions, ripples were washed out and the wave skewness increased, resulting in onshore sediment transport under a sheet flow regime. This suggests that ripple formation and migration can have little impact on the cross-shore supply of sediment from the lower shoreface to the upper shoreface and that more energetic wave conditions are required to significantly transport sediment towards the beach. Highlights: High-resolution observations on the seabed reveal 2D and 3D wave vortex ripples in a macrotidal sandy lower shoreface. The morphological ripple transitions provide assessment of sediment transport regime thresholds. The hypothesis of ross-shore sediment supplied from the lower to the upper shoreface through ripple migration is not supported.